Male circumcision should be promoted in developing countries as a major means of HIV prevention - Ali, F; Vishal, M (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
DOI: 10.3126/saarctb.v7i1.3958 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(1) 19-21